Identifying Predictors of Stress and Job Satisfaction in a Sample of Merchant Seafarers Using Structural Equation Modeling - McVeigh, Joanne; MacLachlan, Malcolm; Vallières, Frédérique; Hyland, Philip; Stilz, Rudiger; Cox, Henriette; Fraser, Alistair (Frontiers in Psychology, 2019)
Background: Seafarers are amongst occupational groups with the highest risk for stress, a factor known to impact on mental health. Psychological issues such as depression, anxiety, suicide, and alcohol or drug dependence are recognised health problems within the maritime sector. The primary aim of this study was to identify which individual and occupational factors, known to impact on psychological functioning across the maritime industry and other sectors, best predict perceived stress and job satisfaction among a sample of merchant seafarers. Methods: Secondary data analysis was conducted using a work experiences and attitudes questionnaire administered by a large shipping company to seafarers within their organisation. Structural equation modelling was conducted using a proposed theoretical model of perceived stress and job satisfaction in a sample of merchant seafarers. Results: While the structural equation model produced acceptable fit to the sample data according to numerous goodness-of-fit statistics, the comparative fit index and Tucker-Lewis index results indicated less than satisfactory model fit. The model explained 23.8% of variance in the criterion variable of perceived stress, and the strongest predictive effect was for dispositional resilience. The model explained 70.6% of variance in the criterion variable of job satisfaction, and the strongest predictive effect was for instrumental work support. Conclusion: When addressing the psychosocial well-being of merchant seafarers, findings of this study suggest that dispositional resilience may be a particularly important factor with regards to perceived stress, while instrumental work support appears to be a critical factor in relation to job satisfaction. Importantly, however, an overall work environment that is perceived by employees as supportive, equal and just is a cornerstone for the psychosocial well-being of seafarers.